The influence of historical motivation of local tourism employees on service quality and long-term industry retention intention - Sengkey, Fenny; Anggayana, I Wayan Agus; Osin, Rosvita Flaviana (Priviet Social Sciences Journal, 2026)
This study analyzes the evolution of motivation among local employees within the Indonesian tourism sector, particularly in Bali, utilizing a temporal narrative qualitative approach. The primary goal is to map how the interplay between historical motivation (past), current work motivation (present), and long-term career aspirations (future) collectively affects Service Quality and Retention Intention within the industry. Data were gathered through in-depth narrative interviews focusing on the experiences of My Past, My Present, and My Future from 14 tourism employees. The thematic analysis revealed that employee motivation is not static but evolves incrementally. It begins with extrinsic factors rooted in family, the desire to make parents proud and reciprocate their sacrifices, and the drive for self-validation serving as an initial anchor of resilience. This external motivation is subsequently internalized in the present phase into Intrinsic Regulation, manifested through Discipline, Consistency, and Self-Improvement. This discipline and consistency are crucial prerequisites for delivering stable service quality (deep acting) on the frontlines. Furthermore, Long-Term Retention Intention is driven by a broader vision: Purpose-Driven Motivation. In this final phase, future aspirations transcend personal financial gain, focusing instead on Social Impact, Job Creation, and Legacy for the Community. This temporal model asserts that employee retention in the tourism industry, which is highly susceptible to high turnover rates, can be significantly enhanced not only through compensation but also by aligning organizational goals with the individual's search for meaning and social contribution.